2017
DOI: 10.3390/ijms18030500
|View full text |Cite|
|
Sign up to set email alerts
|

The Expression and Functional Significance of Runx2 in Hepatocellular Carcinoma: Its Role in Vasculogenic Mimicry and Epithelial–Mesenchymal Transition

Abstract: The transcription factor Runx2 has been reported to promote epithelial-mesenchymal transition (EMT) in many tumors. Vasculogenic mimicry (VM) is described as the mimicry of endothelial cells by tumor cells to form microvascular tubes in aggressive tumors. Galectin-3 has been reported to regulate cell invasion, migration, and VM formation; it could be regulated by Runx2. However, the relationship between Runx2, Galectin-3, EMT, and VM has not been studied in hepatocellular carcinoma (HCC). We examined Runx2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…EMT is regulated by many transcription factors, including the traditional factor ZEB1. The role of EMT in the development of VM has recently attracted attention (9,15,16). Liu et al (8) confirmed that ZEB1 can promote VM formation by inducing EMT in colorectal cancer.…”
Section: Vasculogenic Mimicry In Bladder Cancer and Its Association Wmentioning
confidence: 82%
See 1 more Smart Citation
“…EMT is regulated by many transcription factors, including the traditional factor ZEB1. The role of EMT in the development of VM has recently attracted attention (9,15,16). Liu et al (8) confirmed that ZEB1 can promote VM formation by inducing EMT in colorectal cancer.…”
Section: Vasculogenic Mimicry In Bladder Cancer and Its Association Wmentioning
confidence: 82%
“…Some regulatory factors, such as Twist, Runx2 and ZEB2, play important roles in VM formation by promoting EMT (6,16,17). As a crucial EMT-inducer, ZEB1 was increased in colorectal carcinoma samples and its expression concomitantly occurred with EMT features in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…66 In hepatocellular carcinoma (HCC), Runx2 could promote EMT and VM formation, and Galectin-3 might play a role in this process. 67 Another study investigated VM formation and the EMT phenomenon in two HCC cell lines, MHCC97-H and HepG2, with high and low Notch1 expression, respectively, and confirmed that Notch1 could promote HCC progression by activating the EMT pathway and VM formation. 68 In colon cancer cells, the downregulation of hypoxia-inducible factor 1-alpha (HIF-1α), which functions as a master transcriptional regulator of the adaptive response to hypoxia, could reduce VM and the expression of EMT markers, such as E-cadherin, claudin-4, Vim, and Fn1, in HCT-116 cells.…”
Section: Epithelial-mesenchymal Transition and Vasculogenic Mimicrymentioning
confidence: 87%
“…2B). PAS/CD34 staining was used to better distinguish VM from general endothelium-dependent blood vessels [30-34]. ST2 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%